A cross-diffusion model of effects of norepinephrine on immune response to human immunodeficiency virus. (2018) - Samuel, Shikaa; Gill, Vinod
In this paper, the effects of norepinephrine on immune response to human immunodeficiency virus (HIV) have been modelled using a system of partial differential equations capturing both random and directed movement of immune cells. The equilibrium point of the kinetic system is evaluated and found to be asymptotically stable while the parameter values were obtained from the existing literature. Numerical simulations are performed in order to examine the impact of norepinephrine concentration of antigen presentation process and activation cytotoxic T cells.